Physicochemical Profile and Stability of Red Ginger (Zingiber officinale var. rubrum) SNEDDS as Potential Aphrodisiac - Pratama, Edo; Aly, M. Ainun Najib; Istiqamah, Farida; Widyowati, Retno; Sukardiman, Sukardiman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study investigated the stability of a Self-Nanoemulsifying Drug Delivery System (SNEDDS) formulated with Zingiber officinale var. rubrum (red ginger) extract. SNEDDS formulations, composed of an oil phase, co-surfactant, and surfactant, are designed to create stable isotropic mixtures, critical for drug delivery systems. Prior to assessing long-term physical stability, the optimal Z. officinale var. rubrum SNEDDS preparation underwent comprehensive characterization, including evaluation of emulsification time, pH, particle size, polydispersity index (PDI), and zeta potential. Subsequent physical stability assessments involved rigorous centrifugation, hot-cold, and freeze-thaw cycles. The results demonstrated an emulsification time of ≤1 minute, a pH value of 5.04±0.05, and a particle size of 14.92±0.7 nm, indicative of a nanoscale dispersion. The PDI was 0.282, and the zeta potential was −18.57±1.30 mV, suggesting good colloidal stability. Crucially, throughout six cycles of centrifugation, hot-cold, and freeze-thaw stress tests, the Z. officinale var. rubrum extract SNEDDS exhibited no signs of phase separation, sedimentation, cracking, or creaming. These findings collectively confirm that the prepared Z. officinale var. rubrum extract SNEDDS meets critical physicochemical characteristics and demonstrates excellent physical stability, positioning it as a promising candidate for further development as a natural extract delivery system.